2010
DOI: 10.1111/j.1365-294x.2010.04950.x
|View full text |Cite
|
Sign up to set email alerts
|

Putative causes and consequences of MHC variation within and between locally adapted stickleback demes

Abstract: Genes of the major histocompatibility complex (MHC) have been a source of considerable research interest, owing in large part to the growing body of evidence that they may be subject to both natural and sexual selection. However, much remains to be learned about the dynamics of MHC genes in subdivided populations, particularly those characterized by divergent ecological pressures. In this study, we attempt to disentangle the relative roles of both parasite-mediated selection and MHC-mediated mate choice in an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 107 publications
2
29
0
Order By: Relevance
“…Balancing selection on the MHC has been demonstrated in a number of other systems in other contexts (reviews: Eizaguirre & Lenz, ; Fijarczyk & Babik, ; Piertney & Oliver, ; Sommer, ). An interesting parallel exists between our study and that of the threespine stickleback from the St. Lawrence River estuary (McCairns, Bourget, & Bernatchez, ), which showed evidence of diversifying selection (higher rate of nonsynonymous mutations than synonymous mutations) in freshwater populations, yet not in marine populations (McCairns et al., ). This result was found despite a higher diversity of parasite taxa in the marine fish, suggesting that MHC diversity may be related to the specific parasites present and not parasite diversity.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Balancing selection on the MHC has been demonstrated in a number of other systems in other contexts (reviews: Eizaguirre & Lenz, ; Fijarczyk & Babik, ; Piertney & Oliver, ; Sommer, ). An interesting parallel exists between our study and that of the threespine stickleback from the St. Lawrence River estuary (McCairns, Bourget, & Bernatchez, ), which showed evidence of diversifying selection (higher rate of nonsynonymous mutations than synonymous mutations) in freshwater populations, yet not in marine populations (McCairns et al., ). This result was found despite a higher diversity of parasite taxa in the marine fish, suggesting that MHC diversity may be related to the specific parasites present and not parasite diversity.…”
Section: Discussionsupporting
confidence: 73%
“…That study only examined two populations, however, so it is unclear whether these allelic differences were due to divergent selection between environments (McCairns et al. ). In sockeye salmon ( Oncorhynchus nerka ), significant MHC II β variation existed among beach, river, and stream ecotypes from multiple locations, and this variation was 30 times greater than variation at neutral SNP loci, suggesting divergent selection among ecotypes at this locus (Larson, Seeb, Dann, Schindler, & Seeb, ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, recent studies have reported possible local adaptations of MHC‐based mate choice from natural populations (McCairns et al . ; Evans et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with an intermediate number of alleles are more resistant to infection (Kurtz, Kalbe, & Aeschlimann, ; Wegner, Kalbe, Schaschl, & Reusch, ), harbour fewer parasites (Wegner et al., ), build better quality nests (Jager, Eizaguirre, & Griffiths, ), survive better (McCairns, Bourget, & Bernatchez, ; Wegner, Kalbe, Milinski, & Reusch, ) and attain higher lifetime reproductive success (Kalbe, Eizaguirre, & Dankert, ). Divergent selection is supported because MHC IIβ allele differ between (i) co‐occurring benthic and limnetic stickleback species pairs (Matthews et al., ), (ii) closely parapatric estuarine stickleback in Quebec (McCairns et al., ) and (iii) lake and river stickleback from northern Germany (Rauch et al., ; Reusch, Wegner, & Kalbe, ). Experimental transplants of laboratory‐bred F2 hybrids between German lake/river populations revealed that local MHC alleles conferred higher growth, but no systematically higher infection rate (Eizaguirre et al., ).…”
Section: Introductionmentioning
confidence: 99%